Study of STEM Based on Local Wisdom in Hoening Science Process Skills in the 21st Century Era - Latifatun Mukaromah; Ali Mustadi; Ana Nisa (Postgraduate, University of Mataram, 2022)
The purpose of this study was to examine the topic of STEM based on local wisdom in honing science process skills in the 21st century era. This study used a literature review research design. The population of this article is 100 journals found both internationally and nationally. The sample of this article is 15 journals found based on criteria with 10 international journals and 5 national journals. The results of this study are STEM learning based on local wisdom can increase creativity, critical thinking, process skills, and can train students for skills in Indonesia. The conclusion of this study is that STEM learning based on local wisdom can be an alternative in honing process skills in the 21st century era.